The Effect of Deworming on Growth in One-Year-Old Children Living in a Soil-Transmitted Helminth-Endemic Area of Peru: A Randomized Controlled Trial - Joseph, Serene A. (PLoS Negl Trop Dis, 2015)
BACKGROUND: Appropriate health and nutrition interventions to prevent long-term adverse effects in children are necessary before two years of age. One such intervention may include population-based deworming, recommended as of 12 months of age by the World Health Organization in soil-transmitted helminth (STH)-endemic areas; however, the benefit of deworming has been understudied in early preschool-age children. METHODOLOGY/PRINCIPAL FINDINGS: A randomized, double-blind, placebo-controlled trial was conducted to determine the effect of deworming (500 mg single-dose crushed mebendazole tablet) on growth in one-year-old children in Iquitos, Peru. Children were enrolled during their routine 12-month growth and development clinic visit and followed up at their 18 and 24-month visits. Children were randomly allocated to: Group 1: deworming at 12 months and placebo at 18 months; Group 2: placebo at 12 months and deworming at 18 months; Group 3: deworming at both 12 and 18 months; or Group 4: placebo at both 12 and 18 months (i.e. control group). The primary outcome was weight gain at the 24-month visit. An intention-to-treat approach was used. A total of 1760 children were enrolled between September 2011 and June 2012. Follow-up of 1563 children (88.8%) was completed by July 2013. STH infection was of low prevalence and predominantly light intensity in the study population. All groups gained between 1.93 and 2.05 kg on average over 12 months; the average difference in weight gain (kg) compared to placebo was: 0.05 (95% CI: -0.05, 0.17) in Group 1; -0.07 (95%CI: -0.17, 0.04) in Group 2; and 0.04 (95%CI: -0.06, 0.14) in Group 3. There was no statistically significant difference in weight gain in any of the deworming intervention groups compared to the control group. CONCLUSIONS: Overall, with one year of follow-up, no effect of deworming on growth could be detected in this population of preschool-age children. Low baseline STH prevalence and intensity and/or access to deworming drugs outside of the trial may have diluted the potential effect of the intervention. Additional research is required to overcome these challenges and to contribute to strengthening the evidence base on deworming. TRIAL REGISTRATION: ClinicalTrials.gov (NCT01314937)